2018
DOI: 10.21276/ijcmr.2018.5.5.21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Sexually Transmitted Diseases in a Tertiary Care Hospital in Chamba, Himachal Pradesh

Abstract: Introduction: Sexually transmitted infections (STIs) majorly affect the reproductive age group and results into dire consequences like ano-genital cancer, ectopic pregnancy, foetal wastage, infertility and premature death. Additionally, STIs are associated with increased risk of transmission of Human immunodeficiency Virus (HIV). Epidemiological study is the key to understand the prevailing disease pattern, required for better implementation of policy, and targeted intervention needed to control the progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The most common age group with STI in this study was between 21 and 30 years (mean 27.8±8.8 years) similar to the other studies done in Nepal [5][6][7][8] and India. [9][10][11] The age of sexual exposure and sexual behavior in Nepal has not probably changed in the last two decades, despite there being a sea of changes in urbanization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common age group with STI in this study was between 21 and 30 years (mean 27.8±8.8 years) similar to the other studies done in Nepal [5][6][7][8] and India. [9][10][11] The age of sexual exposure and sexual behavior in Nepal has not probably changed in the last two decades, despite there being a sea of changes in urbanization.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,9 A study in India has shown a minor female predominance. 10 Fewer female cases could be due to fewer symptoms and asymptomatic infections of non-visible parts of the urogenital tract like the cervix.…”
Section: Discussionmentioning
confidence: 99%